Peninsula de Yucatán: causas y manifestaciones del difícil establecimiento de un orden étnico colonial en la región, 1528- 1824 - Baraona Cockerell, Miguel David (Revista de historia., 2010)
This essay contrasts the Spanish conquest and colonization of the Maya lowlands to the complex civilization of Central Mexico, it proposes that the characteristics of agro-ecological Maya systems, which required certain social practices and forms of territorial mobility, clashed with predominant colonial schemes of domination. The study analyzes the interactions between the Maya Society , agro-productive systems, epidemics, and interethnic relations.